(untitled) (World Bulletin of Social Sciences, 2024)
In this article, the role, problems and solutions in the history of the new visual art of Uzbekistan and the analysis of the artworks of famous artists of Uzbekistan, in the spiritual growth of young painters and pedagogues were discussed.